Peran Media 3D Interaktif Berbasis Gamifikasi Terhadap Hasil Belajar Peserta Didik Sekolah Dasar: Systematic Literature Review - Adila Naswa Kurniardi; Chairul Amriyah; Yudesta Erfayliana (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Technology-based learning media has increasingly become an alternative for improving the quality of learning in elementary schools. This systematic literature review aims to synthesize empirical findings on the role of gamification-based interactive 3D media in improving elementary school students' learning outcomes, identify factors that support or hinder its effectiveness, and formulate an implementation framework for classroom learning. The study adapted the PRISMA 2020 and PRISMA-S guidelines to guide literature identification, screening, eligibility assessment, and inclusion. Article searches were conducted through Scopus, Google Scholar, Crossref, and Semantic Scholar using keywords related to interactive 3D media, gamification, learning outcomes, student engagement, and elementary schools. Of the 2,997 records initially identified, 8 core studies met the inclusion criteria and were analyzed thematically. The synthesis shows that gamification-based interactive 3D media contributes positively to students' cognitive, affective, and skills-based learning outcomes by improving motivation, engagement, conceptual understanding, retention, and meaningful learning experiences. The effectiveness of this media is influenced by visual design quality, relevant game elements, teacher readiness, student digital literacy, and the availability of technological infrastructure. However, limited devices, uneven access to technology, low digital literacy, and the complexity of media development remain important barriers. This review concludes that gamification-based interactive 3D media can support innovative elementary learning when its design is pedagogically aligned, accessible, and accompanied by teacher readiness and adequate school infrastructure.